Mobility-aware cross-layer routing for peer-to-peer networks. (January 2019) - Deokate, Balu; Lal, Chhagan; Trček, Denis; Conti, Mauro
Abstract: In remote locations, the best way to establish a communication infrastructure is to deploy Peer-to-Peer (P2P) network over Mobile Ad-hoc Network (MANET). However, the node mobility and efficient cross-layer communication between the overlay and MANET routing protocols remains a challenge for reliable data transmission. In this paper, we propose a novel Mobility Aware Cross-layer Routing approach for Peer-to-Peer Networks (MACARON) over MANET. MACARON provides reliable communication and high lifetime routes to support efficient data transmission in the network. For this purpose, it uses cross-layer communications to share routing updates between MANET and overlay routing protocols. MACARON provides guaranteed routes with low path stretch by maintaining O ˜ ( n ) routing entries per node, where n is the number of nodes in the network. It provides scalability without using any landmark directory to store routing state, and it can effectively handle moderate mobility by using Last Encounter Routing (LER) protocol.